Pengaruh Bentuk Geometri Horizontal Terhadap Perilaku Struktur Gedung Bertingkat 4 Lantai - Siti Nurhayati Safi’i; Rahmani Kadarningsih; Mirzan Gani (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
In the construction of multi-story buildings, improvisation is often carried out on the shape of the building due to land limitations and differences in space functions, and also to meet the needs of architects. Improvised building form means the building has an irregular geometric shape horizontally or vertically. This research analyzes the effect of horizontal geometry shape on the structural behavior of a 4-story high-rise building with 5 variations of T-shaped modeling based on the ratio of Lx and Ly. A comparison of structural behavior in this research was carried out on Model 3 based on base shear, displacement, and drift. The study's results discovered the effect of increasing the span length on the X-direction earthquake load and the Y-direction earthquake load, causing an increase in the base shear, displacement, story drift, and a decrease in stiffness for all modeling variations against Model 3 Meanwhile, the largest increase and decrease were in Model on the Y-direction earthquake load, with an increase in the base shear value of 113.548%, a displacement value of 112.615%, an average story drift value of 28 521%, and a decrease in stiffness of 30.723%.